2014
DOI: 10.5966/sctm.2013-0158
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA- Versus Retrovirus-Based Induced Pluripotent Stem Cell Reprogramming Strategies: Analysis of Genomic Integrity

Abstract: The use of synthetic messenger RNAs to generate human induced pluripotent stem cells (iPSCs) is particularly appealing for potential regenerative medicine applications, because it overcomes the common drawbacks of DNA-based or virus-based reprogramming strategies, including transgene integration in particular. We compared the genomic integrity of mRNA-derived iPSCs with that of retrovirus-derived iPSCs generated in strictly comparable conditions, by single-nucleotide polymorphism (SNP) and copy number variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…These data indicate the presence of a large de novo uniparental disomy (UPD) of the long arm of chromosome 1 from position 144,988,936 to position 249,143,646 (i.e., 104 Mb including 1,087 genes) (OMIM database). Importantly, no UPD was detected in the seven other iPSC lines derived from the same fibroblasts that were analyzed in parallel (five mmRNA‐derived and two retroviral‐derived hiPSC lines) [8]. In order to assess the presence of the UPD in the initial population of fibroblasts, three detection attempts were performed in two different samples of the fibroblasts that were used for reprogramming (at passage 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate the presence of a large de novo uniparental disomy (UPD) of the long arm of chromosome 1 from position 144,988,936 to position 249,143,646 (i.e., 104 Mb including 1,087 genes) (OMIM database). Importantly, no UPD was detected in the seven other iPSC lines derived from the same fibroblasts that were analyzed in parallel (five mmRNA‐derived and two retroviral‐derived hiPSC lines) [8]. In order to assess the presence of the UPD in the initial population of fibroblasts, three detection attempts were performed in two different samples of the fibroblasts that were used for reprogramming (at passage 6).…”
Section: Resultsmentioning
confidence: 99%
“…The generation, characterization, and culture conditions of the mmRNA‐derived hiPSC lines have been fully described [8]. Briefly, human foreskin fibroblasts (ATCC, CRL 2097) were transfected daily with a homemade mmRNA cocktail encoding OCT4, SOX2, KLF4, c‐MYC, and LIN28 (stoichiometry 3:1:1:1:1) following a protocol adapted from Warren et al [9].…”
Section: Methodsmentioning
confidence: 99%
“…Many approaches aiming at the initiation of exogenous protein expression in cells use DNA‐ or RNA‐based viral and nonviral vectors, such as retroviruses , adenoviruses , piggyBac transposons , Epstein‐Barr virus‐based episomal plasmids , Sendai viruses (SeV) , synthetic self‐replicating RNA replicons , or IVT mRNAs for gene transfer. However, due to the integration of transgenes into the host genome in case of retroviral vectors and the resulting high risk of permanent mutagenesis, there are safety concerns against the use of genome integrating vectors for human therapies . Furthermore, the residual expression and reactivation of exogenously delivered transgenes , and immunogenicity are additional problems related to integrating vectors , which limit their clinical application.…”
Section: Advantages and Challenges Of The Exogenous Delivery Of Ivt Mrnamentioning
confidence: 99%
“…It was demonstrated that mRNA‐derived iPSCs more faithfully recapitulated the global transcriptional signature of human ESCs than retrovirus‐derived iPSCs [9]. Furthermore, Steichen et al compared the genomic integrity of retrovirus‐derived iPSCs with that of mRNA‐derived iPSCs. Single nucleotide polymorphism analysis of mRNA‐derived iPSCs did not differ from the original source (parental fibroblast), whereas retrovirus‐derived iPSCs did.…”
Section: Applications Of Ivt Mrnamentioning
confidence: 99%
“…There is evidence that they retain residual epigenetic memory typical of parental somatic cells , which may lead to bias in their propensity to differentiate to different lineages . Although a variety of alternative reprogramming techniques have been developed, including use of mRNAs, miRNAs, proteins, and small molecules , only few have been reported as superior to the original integrative viral vector‐based methods in terms of genetic stability . However, a comparison between lentiviral encoded transcription factor‐mediated reprogramming of germline stem cells (GSC) to iPSCs, to culture condition‐mediated reprogramming of the same GSC lines, demonstrated that the two methods were similar in both the retention of epigenetic marks characteristic of GSC and the incidence of epigenetic errors attributable to the reprogramming process.…”
Section: Induced Pluripotent Cellsmentioning
confidence: 99%